Growth and marketable yield of lettuce (Lactuca sativa L.) as affected by bio-slurry and chemical fertilizer application - Tsigereda Meskelu; Abate Feyissa Senbeta; Yadessa Gonfa Keneni; Getachew Sime (Heliyon, 2024)
The objective of this study was to evaluate the effects of bio-slurry (BS) and chemical fertilizer (CF) application on the growth and yield of lettuce (Lactuca sativa L. var. Parris Iceland Cos). Field experiment consisting of six treatments (100 % BS, 75 % BS + 25 % CF, 50 % BS + 50 % CF, 25 % BS + 75 % CF, 100 % CF and the control) was laid out in a randomized complete block design with three replications. Results showed that the combined application of BS and CF significantly increased lettuce yield and its constituents at p < 0.05. More specifically, the maximum plant height (31.4 cm), leaf area (4914.5 cm2), and yield (38.34 ton ha−1) were obtained with the combined application of 75 % CF and 25 % BS. Aside from that, yield and its components showed a positive correlation. Using BS alone or in combination with CF could increase lettuce yield while also potentially saving money on CF purchases. Overall, combining CF and BS in a 3:1 ratio could be an optimum rate for growing lettuce in the study area.